Variety use and preferences among smallholder sweetpotato farmers and how best to improve their access to quality seed: A gendered perspective and implications for breeding program design - Bayiyana, I.; Okello, J.J.; Ojwang, S.O.; Mulwa, C.K.; Shikuku, Kelvin Mashisia; Mayanja, S.; Ssali, R.T.; Namanda, S.; Kemigisha, D.; Lagerkvist, Carl Johan (CAB International, 2025)
Uganda is a secondary centre of diversity of sweetpotato with most farmers maintaining at least four varieties in their fields. However, most of these varieties are landraces, with the uptake of improved sweetpotato varieties being quite low in the country, especially among women. Efforts to decrease the gender technology adoption gap are critical for inclusive impacts of innovations. This study aims to understand gendered drivers of sourcing and use of sweetpotato varieties among smallholder farmers exposed to behavioural interventions in Uganda. Key informant interviews (KII), focus group discussions (FGDs) and semi-structured interviews (SSI) were used to gather baseline information from farmers located in communities that received behavioural interventions. The results indicate that while men sourced seed-vines mainly from purchasing in the market, women farmers did so mainly from social networks including fellow farmers or neighbours. Men had higher tendency to source vines from the market likely because of higher mobility than women. Consumption traits, especially quality characteristics were strongly associated with variety use. Notably, sweet taste played a big role and was linked to preference for Iboi, Ejumula and Kakamega, the leading varieties. This was followed by high root yield. The challenges women face in sweetpotato production included limited labour force and shortage of farm equipment/machinery, lack of timely access to planting material at on-set of rains, and lack of access to affordable/ cost of improved varieties. These findings highlight the importance of paying attention to both quality and agronomic traits, and not only the latter, in variety development. They also suggest the need for implementation of effective promotional strategies including demonstration gardens, technical backstopping to extensionists to equip them, radio talk shows and market linkages.